Euros and Europeans monetary integration and the European model of society - Martin, Andrew 1929-; Ross, George 1940- (Cambridge University Press, 2004)
Economic and Monetary Union (EMU) is one of the most important developments in modern European politics. Building on two decades of monetary integration it transfers monetary policy, a core function of the modern state, to an independent European Central Bank (ECB) and limits member states' fiscal policy discretion. The ECB insists that growth and employment depend on 'flexibilizing' Europe's labor markets through deep reforms of the social policies and employment relations which comprise the 'European social model'. Member states retain authority over these areas at the heart of national politics, but how will EMU affect the domestic politics of institutional change? Will EMU reinforce de-regulation and retrenchment or will it facilitate reforms that maintain the protections against economic insecurity, inequality, and unilateral employer power the European model has provided? To address these questions, a transatlantic team of leading experts analyzes the evolving tensions between monetary integration and national social policies